(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Use of probabilistic approach for estimating of synoptic-scale abnormality is shown. Anomalous deviations of real in situ Lake Ladoga surface temperatures from typical ones were estimated with the data obtained during 43 expeditions 1960 – 2003. These deviations were mapped and statistically analyzed. A degree of spatiotemporal abnormality of real temperature fields, its features and heterogeneous character were revealed. The scales of thermal inhomogeneity are obtained from computation of two-dimensional spatial autocorrelation functions within the random function network. Ways of analysis of characteristics of anomalies fields’ correlation ellipses are given. Applicability of the methodology and the results is suggested.